mass 1 accelerates downward at a
so mass 2 accelerates up at a
tension = T
mass 1:
m g - T = m a so 3 g - T = 3 a
mass 2:
T - mg = m a so T = 2 (g+a)
substitute T in mass 1 equation
3 g - 2(g+a) = 3 a
g - 2 a = 3 a
a = g/5 = 9.81/5 = 1.962
You could also use the total mass of 5 and total force of (3-2)g
Two masses are hung are connected by a light cord and hung from a frictionless pulley of negligible mad are shown. Mass m1=3.00kg and mass m2=2.00kg. When the two masses are released from rest, the resulting acceleration of the two masses?
4 answers
2 m/s2
1.46
Mama